CTIM-01. TITLE: PHASE 1B STUDY OF AVELUMAB AND WHOLE BRAIN RADIOTHERAPY (WBRT) IN PATIENTS WITH LEPTOMENINGEAL DISEASE (LMD): PRELIMINARY RESULTS. (14th November 2022) - Pina, Yolanda; Chen, Ann; Arrington, John A; Macaulay, Rob; Tran, Nam; Liu, James; Mokhtari, Sepideh; Li, Jiannong; Law, Vincent; Sahebjam, Solmaz; Ahmed, Kamran; Creelan, Ben; et al.
Abstract: BACKGROUND: LMD from systemic cancer has a dismal prognosis with median survivals of 8-10 weeks. A phase 2 trial of PD-1 inhibitor monotherapy in LMD showed median overall survival (OS) of 3.6 months (Brastianos P et al., 2020). We determined the safety/efficacy of avelumab, a PD-L1 inhibitor with WBRT in patients with LMD (NCT0371768). This combination can treat the tumor directly and increase BBB permeability (Li, 2003; Nordal, 2005) allowing the increased egress of activated T cells into the meninges/CSF. METHODS: Patients received concurrent avelumab 800 mg IV q2 weeks for ≤ 5 cycles (unless PD or unacceptable toxicity) with WBRT 3000 cGy in 10 fractions. Primary endpoints are safety/DLTs and OS at 3 months. Secondary endpoints are CSF T-cell/cytokine profiles (scRNAseq, phosophoproteomics etc.). RESULTS: A total of 15 patients (7 breast, 7 lung & 1 other) were enrolled (n = 13 F, ages 32-79). Pts receiving anti-PD-1/PD-1L/PD-L2/CD137, CTLA-4 therapy ≤ 6 months prior were excluded. Three of 15 patients had grade 3/4 AEs (diarrhea, lymphopenia, decreased WBC count in 3 patients). Seven patients (50%) were alive at 3 or 6 months. The estimated median follow up in 14 patients is 4.75 months (range, 0.92 – 30.05 months, 95% CI is 1.32 19.82). The median PFS is 3.75 months (95% CI = 0.85-15.16) and median OS is 6.89 months (95% CI = 1.18-14.7). CONCLUSIONS: The combination of avelumab and WBRT is safe, well tolerated, and demonstrates encouraging activity in patients with LMD with an OS that is longer than other published series. Multiple platform interrogation of CSF (analysis underway) will determine mechanisms of LMD therapeutic/resistance effects.